Два идентичных салтово-маяцких комплексов - Потапова, Ю.Б.; Прокофьев, Р.В. (Материалы по археологии Северного Причерноморья, 2009)
The article is devoted to materials of two complexes of casual finds of saltovo-majatskaja culture from the Bottom Don area. These complexes have been found out in the spring of 2006 during the building excavations in two enough removed from each other points in the territory of Rostov region. Each complex consists of a wheel-thrown oinochoe jar and a massive weaving weight. The finds are dated within the limits of the middle of the 8th - 9th centuries. There are two variants of interpretation of these complexes. In the first case, the complexes are treated as a display of a certain version of Saltovo burial ceremony, which carriers have been connected with Crimea. The second variant of explanation is connected with economic-household treatment of these complexes. In this case, it is a question of a design from a jug, corked by weaving weight, which could be used for preparation of some drinks by fermentation. The possibility of such assumption is illustrated by the recipe of a honey drink from the Byzantine agricultural encyclopaedia of the 10th century.